The Relationship between Farmer Characteristic and Knowledge towards the Successfulness of Cattle Artificial Insemination (AI) in Aceh Besar District - Julia Kardin; Dasrul Dasrul; Sugito Sugito; Nurliana Nurliana; Teuku Zahrial Helmi (The Faculty of Veterinary Medicine of Syiah Kuala University, 2018)
The purpose of this research was to identify the relationship of characteristic and knowledge of farmers to the successful of artificial insemination (AI) in Aceh Besar Districts. The number of respondents is 93 people from twenty three districts in Aceh Besar, selected purposively as the sample of this research. The instruments used in this research are questionnaire and direct observation in the field, while the observed variables are: farmer characteristics, farmer knowledge and artificial insemination result. The results of this research revealed that the characteristics and knowledge of the farmers were good and showed a real relationship to the successfulness of AI in Aceh Besar Districts. The average service per conception (S / C) in Aceh Besar Districts during 2017 was 1.32 while the conception rate (CR) was 86.36%. The results were in accordance with the standard of general guidance of Upsus Siwab Year 2017.